2006
DOI: 10.1161/01.str.0000198887.81948.74
|View full text |Cite
|
Sign up to set email alerts
|

Are There Patients With Acute Ischemic Stroke and Atrial Fibrillation That Benefit From Low Molecular Weight Heparin?

Abstract: Background and Purpose-Treatment doses of heparins are not recommended for acute ischemic stroke. Despite this, their use in this setting is widespread. We investigated whether subgroups of patients with acute ischemic stroke and atrial fibrillation, identified by clinical, hemostatic (D-dimer, prothombin fragments 1ϩ2 [F 1ϩ2 ], soluble fibrin monomer), or inflammatory (C-reactive protein [CRP]) variables might have a differential response to low molecular weight heparin (LMWH) over aspirin. In addition, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…hsCRP has been shown to be a prognostic indicator in patients with ACS as well as in those with nonselective ischemic stroke [21,22]. To the best of our knowledge, however, this is the first report suggesting that high hsCRP might be a predictor of symptomatic HTr in ACS.…”
Section: Discussionmentioning
confidence: 96%
“…hsCRP has been shown to be a prognostic indicator in patients with ACS as well as in those with nonselective ischemic stroke [21,22]. To the best of our knowledge, however, this is the first report suggesting that high hsCRP might be a predictor of symptomatic HTr in ACS.…”
Section: Discussionmentioning
confidence: 96%
“…604 A subsequent subgroup analysis did not demonstrate any group of patients who would have benefited from dalteparin. 619 Similar trials of certoparin and tinzaparin demonstrated no differences in the rates of favorable outcomes. 620,621 Intravenous administration of danaparoid (heparinoid/ORG 10172) using a bolus to initiate therapy was tested in a randomized, double-blind, placebo-controlled trial.…”
Section: Lower-molecular-weight Heparins and Danaparoidmentioning
confidence: 91%
“…Despite lacking evidence [9, 10], many institutions and treating physicians therefore continue to treat AF patients on ‘an individual basis’ with heparin [11,12,13]. …”
Section: Introductionmentioning
confidence: 99%